Public Service Management Approach to Teaching Factory Design at SMK Wahidin Cirebon for Soft Skills Improvement through Work Culture in Retail Education - Nurhasanah, Nurhasanah; Ahman, Eeng; Dahlan, Dadang; Mulyadi, Hari (Jurnal Manajemen Pelayanan Publik, 2025)
This research purposed to design a Teaching Factory (TeFa) learning model based on work culture principles to enhance students’ soft skills in retail education, focusing on Public Service Management and Organization. The research was conducted at SMK Wahidin Cirebon and partner vocational schools, the model provided students with hands-on experience in authentic, service-oriented retail activities reflecting real workplace environments. The study used a Research and Development (R&D) approach, adapting Borg & Gall’s (2003) model into a Four-D Model (Define, Design, Develop, Disseminate). Participants included 396 11th-grade Retail Business students from SMK Wahidin Cirebon and five vocational schools in West Java. The model integrated Kaizen-based work culture; which are Seiri, Seiton, Seiso, Seiketsu, and Shitsuke; into teaching factory learning to simulate public service industry standards. Validation confirmed that the TeFa BK model met quality criteria, while trials showed its practicality (teacher performance), effectiveness (improved students’ soft skills), and positive student responses. Students achieved an average soft skills improvement of 18.36 points (p < 0.001), with consistent results across schools. The novelty lies in applying public service management and organization principles within a Kaizen-informed work culture, producing a scalable, effective Teaching Factory model for vocational retail education.